Ferroptosis and ferritinophagy in diabetes complications - Jiahui He; Zhangwang Li; Panpan Xia; Ao Shi; Xinxi FuChen; Jing Zhang; Peng Yu (Elsevier, 2022)
Background: With long-term metabolic malfunction, diabetes can cause serious damage to whole-body tissue and organs, resulting in a variety of complications. Therefore, it is particularly important to further explore the pathogenesis of diabetes complications and develop drugs for prevention and treatment. In recent years, different from apoptosis and necrosis, ferroptosis has been recognized as a new regulatory mode of cell death and involves the regulation of nuclear receptor coactivator 4 (NCOA4)-mediated ferritinophagy. Evidence shows that ferroptosis and ferritinophagy play a significant role in the occurrence and development of diabetes complications. Scope of review: we systematically review the current understanding of ferroptosis and ferritinophagy, focusing on their potential mechanisms, connection, and regulation, discuss their involvement in diabetes complications, and consider emerging therapeutic opportunities and the associated challenges with future prospects. Major conclusions: In summary, ferroptosis and ferritinophagy are worthy targets for the treatment of diabetes complications, but their complete molecular mechanism and pathophysiological process still require further study.